1994
DOI: 10.1093/nar/22.16.3418
|View full text |Cite
|
Sign up to set email alerts
|

Directly labeled DNA probes using fluorescent nucleotides with different length linkers

Abstract: Directly labeled fluorescent DNA probes have been made by nick translation and PCR using dUTP attached to the fluorescent label, Cy3, with different length linkers. With preparation of probes by PCR we find that linker length affects the efficiency of incorporation of Cy3-dUTP, the yield of labeled probe, and the signal intensity of labeled probes hybridized to chromosome target sequences. For nick translation and PCR, both the level of incorporation and the hybridization fluorescence signal increased in paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 15 publications
2
76
0
4
Order By: Relevance
“…The yield was reduced to Ϸ10% for the second incorporation. Others have shown that nucleotide analogs with longer linker arms can be incorporated into DNA templates with significantly higher yields (33). It is also possible to use a more promiscuous polymerase (34,35) or nucleotide analogues whose dye can be chemically removed at each step.…”
Section: Resultsmentioning
confidence: 99%
“…The yield was reduced to Ϸ10% for the second incorporation. Others have shown that nucleotide analogs with longer linker arms can be incorporated into DNA templates with significantly higher yields (33). It is also possible to use a more promiscuous polymerase (34,35) or nucleotide analogues whose dye can be chemically removed at each step.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that some modified DNA polymerases are highly tolerable for nucleotides with extensive modifications with bulky groups such as energy transfer dyes at the 5-position of the pyrimidines (T and C) and 7-position of purines (G and A) (23,24). The ternary complexes of a rat DNA polymerase, a DNA templateprimer, and dideoxycytidine triphosphate have been determined (22), which supports this fact.…”
mentioning
confidence: 56%
“…However, no success has been reported for the incorporation of such a nucleotide with a cleavable fluorescent dye on the 3Ј position by DNA polymerase into a growing DNA strand. The reason is that the 3Ј position on the deoxyribose is very close to the amino acid residues in the active site of the polymerase, and the polymerase is therefore sensitive to modification in this area of the ribose ring, especially with a large fluorophore (22).It is known that some modified DNA polymerases are highly tolerable for nucleotides with extensive modifications with bulky groups such as energy transfer dyes at the 5-position of the pyrimidines (T and C) and 7-position of purines (G and A) (23,24). The ternary complexes of a rat DNA polymerase, a DNA templateprimer, and dideoxycytidine triphosphate have been determined (22), which supports this fact.…”
mentioning
confidence: 99%
“…The amount of probe used for hybridization depends on the array format and labeling method [6]. In a typical hybridization reaction, equal amounts of Cy3-labeled probes based on the incorporated dye concentration are combined [7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%